Records of phlebotomine sand flies (Diptera, Psychodidae, Phlebotominae) with a description of a new species of Sergentomyia França & Parrot from Khao Yai National Park, Thailand - Curler, Gregory R. (Zootaxa, 2011)
Males and females of Sergentomyia phasukae sp. nov., S. bailyi (Sinton), and S. barraudi (Sinton), and females of S. gomboki (Lewis & Wharton) and Phlebotomus (Euphlebotomus) sp. (Diptera, Psychodidae, Phlebotominae) were collected by Malaise traps and CDC traps in Khao Yai National Park, central Thailand. A new species is described and illustrated, collection records for described species are given, and some taxonomic problems concerning the subgenera of Sergentomyia are discussed.